Study of physical and mechanical behavior of artificial lightweight aggregate made of Pakistani clays. (16th May 2023) - Hussain, Fazal; Rehman, Fazal; Khushnood, Rao Arsalan; Ali Khan, Shayan; Hamza, Ameer
Graphical abstract: Highlights: Potential of Pakistani clays for production of artificial lightweight expanded clay aggregate. The addition of kerosene and fly ash has been assessed. Mechanical properties of expanded clay aggregate assessed. Study bloating mechanism of a variety of clays. LWA is an excellent reuse for clay as part of a circular economy. Abstract: This study aims to unravel the potential of Pakistan in the domain of artificial lightweight expanded clay aggregates (ALECA) and investigate the influence of pellets size, firing temperature, and admixture doses on the mechanical properties of ALECA. The five prominent and unfathomed clay fields in Pakistan were chosen. The selected clay fields include Nandipur, Multan, Mirpur, Sibbi, and DIK. After essential geotechnical characterization, the collected soil samples of chosen fields were chemically analyzed using X-ray diffraction and X-ray fluorescence tests, whereas thermal stability was assessed using thermogravimetric analysis. The characterized soil was used in the synthesis of ALECA through 120 different mixes recipes designed by varying pellet sizes, and the dose of admixed fly ash and kerosene oil. The addition of fly ash and kerosene allowed the development of a well-distributed-porous core surrounded by a very thin shell. Nandipur clay turned out to be ideal for bloating, with a bloating index of 33.33 % and a loose bulk density of 0.39 g/cm 3 . These lightweight aggregates will not only help preserve natural mountain reserves but also significantly impact the lifecycle costing of structures.